2007
DOI: 10.1523/jneurosci.5425-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Deprivation Alters Aggrecan and Perineuronal Net Expression in the Mouse Barrel Cortex

Abstract: An important role for the neural extracellular matrix in modulating cortical activity-dependent synaptic plasticity has been established by a number of recent studies. However, identification of the critical molecular components of the neural matrix that mediate these processes is far from complete. Of particular interest is the perineuronal net (PN), an extracellular matrix component found surrounding the cell body and proximal neurites of a subset of neurons. Because of the apposition of the PN to synapses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
234
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(255 citation statements)
references
References 49 publications
17
234
2
2
Order By: Relevance
“…A major redistribution of ␣1 subunits from synaptic to extrasynaptic locations on the cell membrane appears unlikely, because we observed no significant changes in rise times (40). Our finding of increased ␣1 subunit functionality does not rule out additional contributions to altered IPSC properties through presynaptic mechanisms, such as altered structure of presynaptic terminals or the selective loss of specific types of presynaptic inhibitory neurons (12,(40)(41)(42)(43)(44)(45). Interestingly, we do not observe changes in IPSCs in RS cells from whisker-deprived mice (42).…”
Section: Long-term Sensory Deprivation Causes a Switch In Functional contrasting
confidence: 57%
“…A major redistribution of ␣1 subunits from synaptic to extrasynaptic locations on the cell membrane appears unlikely, because we observed no significant changes in rise times (40). Our finding of increased ␣1 subunit functionality does not rule out additional contributions to altered IPSC properties through presynaptic mechanisms, such as altered structure of presynaptic terminals or the selective loss of specific types of presynaptic inhibitory neurons (12,(40)(41)(42)(43)(44)(45). Interestingly, we do not observe changes in IPSCs in RS cells from whisker-deprived mice (42).…”
Section: Long-term Sensory Deprivation Causes a Switch In Functional contrasting
confidence: 57%
“…Experiments using a nonselective blocker of voltage-gated sodium channels, but not transgenic models with compromised glutamate release, clearly inhibited PNN formation (Reimers et al, 2007). Similar observations have also been reported in the visual cortex and barrel cortices (Dityatev et al, 2007;McRae et al, 2007). Dark rearing in newborn cats prolongs the critical period in the visual cortex with a concomitant decrease in aggrecan immunostaining (Hockfield et al, 1990;Lander et al, 1997;Pizzurusso et al, 2002), but in developing chicks light deprivation did not prevent PNN formation (Gati et al, 2010).…”
Section: Activity-dependent Regulation Of Pnn Formationmentioning
confidence: 56%
“…Interestingly, after 30 days of normal activity postwhisker trimming, there is a further reduction in aggrecan-positive PNN levels, implying that experience in first 30 days of life is critical. The decrease appears to be specific to aggrecan, but not other PNN markers, localized specifically around PV-expressing cells (McRae et al, 2007). Sensory deprivation of facial vibrissae in rat barrel cortex also reduced the number of WFA-labeled PNNs (Nakamura et al, 2009).…”
Section: Activity-dependent Regulation Of Pnn Formationmentioning
confidence: 89%
See 1 more Smart Citation
“…However, none of such difference was detected with GFAP or S100 staining or in GFAP-eGFP mice. Finally, the compartmentalized expression of Cxs could be attributable to a difference in the expression of extracellular matrix and/or adhesion molecules reported to occur in the barrel cortex, as for instance the perineuronal net (McRae et al, 2007) or cadherins (Gil et al, 2002). Indeed, such compartmentalized pattern could affect the expression of astrocytic Cxs and GJC because proteoglycans (Spray et al, 1987) and cadherins (Giepmans, 2004) have been reported to control Cx expression and function.…”
Section: Discussionmentioning
confidence: 99%